2017
DOI: 10.1177/0963689717721221
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Mesenchymal Stem Cells from the Elderly Exhibit Decreased Migration and Differentiation Abilities with Senescent Properties

Abstract: Adipose-derived stem cells (ASCs) can be applied extensively in the clinic because they can be easily isolated and cause less donor-site morbidity; however, their application can be complicated by patient-specific factors, such as age and harvest site. In this study, we systematically evaluated the effects of age on the quantity and quality of human adipose-derived mesenchymal stem cells (hASCs) isolated from excised chest subcutaneous adipose tissue and investigated the underlying molecular mechanism. hASCs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(116 citation statements)
references
References 38 publications
7
109
0
Order By: Relevance
“…To further test whether age impacts the functions of ADSCs, we examined the osteogenic differentiation potential of ADSCs with Alizarin Red S staining assay. We found that, in agreement with previous reports (Liu et al, 2017), the differentiation potential was impaired in the old groups of ADSCs in comparison to the young cells ( Figure S12 a-b). However, we did not observe any significant correlation between the differentiation potential and BER efficiency or XRCC1 expression ( Figure S12 c-d).…”
Section: Introduction Re Sults and Discussionsupporting
confidence: 93%
“…To further test whether age impacts the functions of ADSCs, we examined the osteogenic differentiation potential of ADSCs with Alizarin Red S staining assay. We found that, in agreement with previous reports (Liu et al, 2017), the differentiation potential was impaired in the old groups of ADSCs in comparison to the young cells ( Figure S12 a-b). However, we did not observe any significant correlation between the differentiation potential and BER efficiency or XRCC1 expression ( Figure S12 c-d).…”
Section: Introduction Re Sults and Discussionsupporting
confidence: 93%
“…PGC1α lacks DNA-binding activity but interacts with and coactivates several transcription factors including Nrf2, which controls constitutive and inducible expression of an array of antioxidant enzymes including SOD, GST, and catalase [35]. Downregulation of PGC1α has been shown to affect the antioxidant response in Friedreich's ataxia [36] and expression of PGC1α has been noted to be lower in adipose tissue-derived MSC from elderly donors [37]. Interestingly, MSC isolated from patients with PSP had fivefold lower levels of expression of PGC1α compared with control MSC [19] and, in an induced pluripotent stem cell model of Parkinson's disease, S-nitrosylation of the transcription factor myocyte enhancer factor 2c (MEF2C) contributes to mitochondrial dysfunction and apoptotic cell death via dysregulation of the PGC1α-MEF2C transcriptional network [38], a Protein expression of SOD1 in response to nitrostative stress in C-MSC and MS-MSC was examined using immunoblotting.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, only female patients were recruited and no information about ethnicity or lifestyle was collected. The mean age of the recruited donors is 55.5 ± 1.4, and ageing has been shown to increase cellular senescence and AD-MSCs extracted from elderly patients (age 60-73) have been shown to have diminished migration and differentiation capabilities [53]. The molecular mechanisms underlying these changes are not fully understood, so it is not possible to rule out potential changes in the P2 receptor expression and/or functioning as a possible cause.…”
Section: +mentioning
confidence: 98%